Ultrasound colour Doppler is associated with synovial pathology in biopsies from hand joints in rheumatoid arthritis patients: a cross-sectional study. Issue 4 (8th March 2013) - Andersen, Martin; Ellegaard, Karen; Hebsgaard, Josephine B; Christensen, Robin; Torp-Pedersen, Søren; Kvist, Peter H; Søe, Niels; Rømer, John; Vendel, Nina; Bartels, Else Marie; Danneskiold-Samsøe, Bente; Bliddal, Henning
Abstract : Objectives: Little is known regarding the association between ultrasound-determined pathological synovial blood flow and synovial pathology in rheumatoid arthritis (RA). We therefore examined the association between colour Doppler ultrasound imaging and synovitis assessed by histopathology and specific cell markers by immunohistochemistry in patients with RA. Methods: 81 synovial sites from wrist and finger joints from 29 RA patients were evaluated by ultrasound colour Doppler and subsequently biopsied by needle arthroscopy. The association between ultrasound colour fraction and an overall synovitis score and immunohistochemical staining for CD3, CD68, Ki67 and von Willebrand factor was investigated, including repeated samples from the same patients. The overall synovitis score (total 0–9) assessed synovial lining hyperplasia (0–3), stromal activation (0–3) and inflammatory infiltration (0–3). Data were clustered within patients, thus a linear mixed model was applied for the statistical tests. Parsimony in the statistical models was achieved omitting covariates from the model in the case of what was judged no statistical significance (p>0.1). Results: Doppler colour fraction showed an association with the overall synovitis score (approximated Spearman, approximately r=0.43, p=0.003). The density of all immunohistochemical stainings showed a significant association with Doppler colour fraction: von Willebrand factor (approximately r=0.44, p=0.01), CD68 (approximately r=0.53, p=0.02), Ki67 (approximately r=0.57, p=0.05) and CD3 (approximately r=0.57, p=0.0003). Conclusions: Colour Doppler activity is associated with the extent of inflammation present in the synovial biopsies from RA patients. However, synovial pathology was also seen in biopsies taken from Doppler negative sites.